Paleoecology and depositional environment of the Mowry Shale (Albian), Black Hills region - Cluff, Robert M. (My University, 1976)
Content includes information on: previous work, stratigraphy, sedimentary structures, bioturbation, paleontology and depositional environment of the Black Hills.
vi, 104 leaves : ill. ; 29 cm.
Keywords: Geology --Black Hills (S.D. and Wyo.)